Perspective directions of formation of the emotional and valuable attitude of school students towards chemical knowledge. (Journal of Educational Sciences, 2016)
In article the author made an attempt of search of ways of permission of a contradiction between potential opportunities of chemistry as development tools of the valuable sphere of the personality and not formation at school students of the valuable attitude towards chemical knowledge. Relevance of this problem locates obviously expressed tendency of underestimation of values of chemical knowledge that at the modern ultrahigh level of use of achievements of chemistry in society leads to production accidents and, as a result, to active distribution of a сhemophobia. According to the author of article, effective formation of the emotional and valuable attitude of school students towards chemical knowledge will be promoted by representation of chemistry as the fundamental science playing an important role in formation of the personality thanks to the huge axiological potential which is offered to be considered as system of such values – scientific world outlook, educational (humanistic), common cultural, historical, valeological, preventive, practical (applied), nature protection, polytechnic and professionally orientation. It also considerably will facilitate introduction of the axiological (valuable) beginnings to process of teaching chemistry. The author proves importance of axiological function of chemical knowledge, their high rank place in the general outlook of the person and considers that pedagogically transformed «humanized» scientific chemical knowledge has to become a valuable priority in system of chemical formation of XXI centuries.
Keywords: emotional and valuable attitude towards knowledge; values of chemical science; school chemical education; directions and options of approaches to representation of chemical and ecological and ecoethical materials of student’s audience